WORKSHOP ON READ BEAN MOCHI CREATION AT SEKOLAH DIAN HARAPAN DAAN MOGOT - Indra, Febryola; Wijaya, Halim Adi; Patricia, Sharen; Widarson, Nella Nevila (Universitas Pelita Harapan, 2024)
Mochi is a traditional food from Japan that is simple and easy to make. This food has a mildly sweet flavour characteristic with chewy and elastic texture. The filling of mochi that is commonly used is red bean paste, the same which we will held class with in SDH Daan Mogot. It is important to held this PKM to increase the skill of SDH students and familiarize the students about red bean which had never been taught before. For the culinary class which will be held in SDH Daan Mogot we hope to invite the students to participate in the class. The students will learn hands on cooking the red bean mochi while being guided by the instructor chef. In this class, the students will be grouped into 5 person group copying the chef instructor. The committee of the culinary class will provide one copy of the recipe for each group, ingredients, certificates, and souvenirs for the students.